BEBERAPA CATATAN TENTANG ASPEK PERTUMBUHAN, MAKAN DAN REPRODUKSIIKAN NILEM PAITAN (Osteochilus jeruk Hadiaty & Siebert, 1998) - Renny Kurnia Hadiaty (BERITA BIOLOGI, 2000)
Osteochilus jeruk is one of the two new species of Osteochilus occuring in Gunung Leuser National Park, Aceh, Sumatra, Indonesia.It has a big size and beautiful colour, so it is potential as food and aquarium fish. Notes on growth, food and reproduction were examined as base for the culture of this fish.